Caracterización de los desechos sólidos generados en la parroquia de Chugchilán del cantón Sigchos, provincia de Cotopaxi, periodo 2013 - Aguaiza Jácome, Juan Andrés (2014)
This research work mentioned: CHARACTERISATION OF THE SOLID WASTE GENERATED IN THE PARISH OF CHUGCHILÁN OF CANTONE SIGCHOS, PROVINCE OF COTOPAXI, PERIOD 2013, it refers to the solid wastes that pollute our environment. The most frequent risk with relation to the solid leftover is the cause of pollution directly or indirectly that takes place in different aspects in our environment, the principal causer of this contamination is the man in different ways, can be with the household waste, bathrooms, hostels, and the educational centers where primary and secondary are generated quite a few solid wastes that are not classified, nor treated are generated as if it must or at least toss in the filling that has the parish of Chugchilán....